2015
DOI: 10.1007/978-3-319-24574-4_67
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Surface-Based Construction of Individual Structural Network with Application to Early Brain Development Study

Abstract: Analysis of anatomical covariance for cortex morphology in individual subjects plays an important role in the study of human brains. However, the approaches for constructing individual structural networks have not been well developed yet. Existing methods based on patch-wise image intensity similarity suffer from several major drawbacks, i.e., 1) violation of cortical topological properties, 2) sensitivity to intensity heterogeneity, and 3) influence by patch size heterogeneity. To overcome these limitations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Currently, research on SCN-based early brain development patterns of children across the first 5 years of life is still in a nascent stage. Studies have found that in full-term neonates, SCN already exhibits the small-world topology and ordered modular organization (Fan et al, 2011;Meng et al, 2015). During 0-2 years old, the global efficiency, local efficiency, clustering coefficient, and modularity index of SCN constructed based on CT increases with age, and the shortest path length decreases with age (Fan et al, 2011;Meng et al, 2015), which suggest that both network segregation and integration enhances with age.…”
Section: Developmental Patterns During the First Years Of Lifementioning
confidence: 99%
See 2 more Smart Citations
“…Currently, research on SCN-based early brain development patterns of children across the first 5 years of life is still in a nascent stage. Studies have found that in full-term neonates, SCN already exhibits the small-world topology and ordered modular organization (Fan et al, 2011;Meng et al, 2015). During 0-2 years old, the global efficiency, local efficiency, clustering coefficient, and modularity index of SCN constructed based on CT increases with age, and the shortest path length decreases with age (Fan et al, 2011;Meng et al, 2015), which suggest that both network segregation and integration enhances with age.…”
Section: Developmental Patterns During the First Years Of Lifementioning
confidence: 99%
“…Studies have found that in full-term neonates, SCN already exhibits the small-world topology and ordered modular organization (Fan et al, 2011;Meng et al, 2015). During 0-2 years old, the global efficiency, local efficiency, clustering coefficient, and modularity index of SCN constructed based on CT increases with age, and the shortest path length decreases with age (Fan et al, 2011;Meng et al, 2015), which suggest that both network segregation and integration enhances with age. However, a study on infants aged 0-2 years old found that in SCNs constructed based on CT, the global efficiency increases while the local efficiency decreases with age; in SCNs constructed based on curvedness, the global efficiency decreases while the local efficiency increases with age (Nie et al, 2014).…”
Section: Developmental Patterns During the First Years Of Lifementioning
confidence: 99%
See 1 more Smart Citation